Experimental analysis of DI-ZSI based DSTATCOM - Jogeswara Sabat; Mrutyunjaya Mangaraj; Ajit Kumar Barisal; Praveen Kumar Yadav Kundala; Rohan Vijay Thakur (Institute of Advanced Engineering and Science, 2023)
This article presents the dual operation of distributed energy resources (DER) integrated impedance source inverter (DI-ZSI). The distribution grid, DER and variable nonlinear load are operating on two modes. In mode-1, power generated by the DER is zero or less then the load requirement and the inverter act as a voltage source inverter (VSI) for shunt compensation only. But, in mode-2, power generated by the DER greater than the load requirement and operates as a DI-ZSI based distributed static compensator (DSTATCOM). In this scenario, it not only acts as a shunt compensator but also inject active power to the distribution grid. An accurately tuned proportional integral with adaptive least mean square (ALMS) controller is used to generate the switching signals of inverter switches. The DI-ZSI performs stable operation in the distribution grid over a variable non-linear loading. A field programmable gate array (FPGA) SPARTAN-6 controller is used to develop the proposed system. Experimental results from DI-ZSI and VSI under variable loading highlighted the superiority of the DI-ZSI as per guidelines imposed by IEEE-2030-7-2017.